2009
DOI: 10.1111/j.1468-1331.2009.02792.x
|View full text |Cite
|
Sign up to set email alerts
|

Decision‐making in Parkinson’s disease patients with and without pathological gambling

Abstract: Low performance in decision-making under ambiguity and abnormal social behavior distinguished PD patients with PG from those without this disorder. Dopamine replacement therapy may induce dysfunction of the ventromedial prefrontal cortex and amygdala-ventral striatum system, thus increasing the risk for developing PG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
3
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 38 publications
8
83
3
2
Order By: Relevance
“…Compared to PD patients without impulse control disorder (ICDs), PD patients with pathological gambling (PG) showed impaired cognitive impulsivity, i.e. poorer performances on the IGT [66], and preference for immediate over future rewards [67]. Neuroimaging studies have underlined the idea of a susceptibility to impulsivity.…”
Section: Cognitive Impulsivity In Parkinson's Diseasementioning
confidence: 99%
“…Compared to PD patients without impulse control disorder (ICDs), PD patients with pathological gambling (PG) showed impaired cognitive impulsivity, i.e. poorer performances on the IGT [66], and preference for immediate over future rewards [67]. Neuroimaging studies have underlined the idea of a susceptibility to impulsivity.…”
Section: Cognitive Impulsivity In Parkinson's Diseasementioning
confidence: 99%
“…In a recent study of PD patients with and without an ICD, patients with ICDs demonstrated intact stimulus reinforcement learning, but had a strong preference for immediate over future rewards using the delayed discounting task [41]. In a study using the Iowa Gambling Task, PD patients with PG demonstrated greater impairment in decision making compared with PD controls [42]. Another study of PD patients with and without ICD tested on versus off DA treatment reported that only ICD patients demonstrated increased risk taking on the Balloon Analogue Risk Task with DA exposure [43].…”
Section: Cognitive Performance Of Pd Patients With Icdsmentioning
confidence: 99%
“…This is in contrast to PD patients without ICBs who are usually risk averse, anhedonic and low in novelty seeking [42][43][44][45][46]. PD patients with ICB are more aggressive, disinhibited and more antisocial than control PD patients [7,33,47]. Further they have higher schizotypy scores, which measures the risk of psychosis, compared to controls [48].…”
Section: Personality Traits Decision-making and Reward Processing Inmentioning
confidence: 85%